Church and School: A Study of the Impact of Education on Religion - Brothers, Joan (Liverpool University Press, 1964)
This 1964 study makes an important contribution to the sociology of religion, as it enlarges the frontiers of the subject so as to include aspects of human conduct which ware both religious and social. In doing so, it challanges positivist conceptions of sociology and the social sciences more broadly. Joan Brothers's work explores the interaction between the organization, structure, and activities of a church and those of the wider society in which it is places.